Decision Support System for Building Material Supplier Selection using Simple Additive Weighting (SAW) Method - Sipayung, Evasaria Magdalena; Lokasurya, Erik; Kristina, Sonna (Universitas Bunda Mulia, 2022)
XYZ Store is a retail store that sells goods in the form of building materials located in Bandung Regency. This shop sells types of cement products, water pumps and PVC pipes where this shop gets its products by ordering from suppliers. This shop is having difficulty choosing a supplier because it takes time to determine a supplier. Suppliers are contacted by telephone to ask about the availability and price of the building materials needed. If the supplier has the goods, he will buy them immediately and not ask other suppliers. The criteria used in determining suppliers are based on price and availability of goods. The criteria required by this shop are price, product availability, expiry date and delivery speed in accordance with the shop's condition when the goods are needed. The aim of this research is to create a decision support system that can provide supplier recommendations so as to help in selecting suppliers that match the criteria using the Simple Additive Weighting (SAW) method. Supplier selection decision support systems can provide the best alternative suppliers by ranking suppliers with the best performance. This web-based SPK was developed using the programming language PHP, Javascript and using an SQL database.